Preparation method of ultra-high performance concrete railway protection fence column
By adding nano alumina, graphite powder and other modification agents to the concrete columns, a denser structure is formed, which solves the problem of weathering and rust of existing reinforced concrete columns, and achieves high compression, crack resistance and heat resistance The improvement extends the service life.
Patent Information
- Application Number
- CN202411421790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing reinforced concrete railway protective fence columns are prone to weathering and corrosion of steel bars, causing expansion, cracking and falling off, affecting driving safety, and lacking materials with high compression and crack resistance.
Use modified agents to enhance the physical connection of concrete components, including nano-alumina, graphite powder, modified epoxy resin, etc., and combine modified agents such as polycarboxylic acid water reducer and nano-silica to form a denser structure without the need for reinforcement support. , improve crack resistance, deformation resistance and heat resistance.
It significantly improves the compressive strength, crack resistance and heat resistance of the column, extends the service life, avoids structural problems caused by steel bar corrosion, and ensures structural stability in harsh environments.
Smart Images

Figure CN118908641B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultra-high performance concrete columns, in particular to a method for preparing ultra-high performance concrete railway protective fence columns. Background Art
[0002] Concrete railway protection fence posts are an important part of railway safety protection facilities. It is usually made of concrete and has the characteristics of being strong, durable and corrosion-resistant. The main function of these posts is to support and fix the railway protection fence to ensure the safety of the railway line, prevent pedestrians, animals or other objects from entering the railway area, and avoid safety accidents.
[0003] For a long time, the railway Yanbian guardrail columns generally use reinforced concrete structures, which are connected with wire mesh to form a protective fence. However, in actual use, the reinforced concrete columns are easily weathered, and the concrete expands, cracks and falls off due to the corrosion of the steel bars in the concrete. This seriously affects driving safety. In this context, a new material with higher compression and crack resistance is needed. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing ultra-high performance concrete railway protective fence posts. By adding specific modifiers, the physical connection of the components in the posts is enhanced, and there is no need to use steel bars as support, thereby obtaining excellent crack resistance, deformation resistance and heat resistance.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing an ultra-high performance concrete railway protection fence post, comprising the following steps:
[0006] a) Prepare the following raw materials by weight:
[0007] Cement: 350-400 parts;
[0008] Microsilica fume: 50-100 parts;
[0009] Quartz sand: 800-900 parts;
[0010] Improver: 15-30 parts;
[0011] Modifier: 10-20 parts;
[0012] Water: 120-140 parts;
[0013] Water reducing agent: 5-10 parts.
[0014] b) During the mixing process, cement, microsilica powder, quartz sand and water are added in the initial stage and mixed evenly;
[0015] c) Add the improver at a temperature of 25-30°C and continue stirring for 10-15 minutes;
[0016] d) After 10 minutes of stirring, add the modifier and keep stirring to allow the modifier to fully blend with other components;
[0017] e) Pour concrete and let it stand to form. The curing time should be no less than 48 hours in an environment with a curing temperature of 40-60℃ and a curing humidity of no less than 95%;
[0018] f) After curing, the obtained column material has good crack resistance, deformation resistance and heat resistance.
[0019] Preferably, the improver comprises the following components in parts by weight:
[0020] Silica fume: 35-40 parts;
[0021] Graphite powder: 15-20 parts;
[0022] Nano-alumina: 20-25 parts;
[0023] Modified epoxy resin: 10-15 parts.
[0024] The components are mixed by uniform stirring and heating to 50-60°C, then cooled and stirred uniformly before use. The addition of the modifier reacts with the chemical substances of the cement hydration reaction (such as calcium hydroxide) to produce denser products (such as ettringite, CSH gel). These products not only fill the pores, but also improve the crystal structure of the material, so that the column material still has high strength without the use of steel bars. At the same time, the introduction of nano-alumina will also enhance the bonding force of the crystal interface, reduce porosity, and improve the overall density and compressive strength.
[0025] Preferably, the modifier comprises the following components in parts by weight:
[0026] Polycarboxylate water reducer: 25-35 parts;
[0027] Reinforced cellulose: 20-30 parts;
[0028] Nano silicon dioxide: 15-20 parts;
[0029] Trace perovskite crystals: 5-10 parts.
[0030] The polycarboxylate water reducer in the modifier forms a steric hindrance effect by adsorbing on the surface of cement particles, reducing direct contact and agglomeration between cement particles, and improving the fluidity and uniformity of cement paste. Nano-silica reacts with calcium hydroxide in cement to generate more CSH gel, which increases the strength and density of the cement matrix. Reinforced cellulose forms a microfiber-like structure in the material, improving the tensile and bending properties of the material and significantly enhancing crack resistance.
[0031] Preferably, the improver is added at a temperature of 25-30° C., and the stirring time is controlled at 10-15 minutes to ensure full fusion of the components.
[0032] Preferably, the modifier is added 5-10 minutes after the improver is added, and the stirring speed is controlled at 100 revolutions per minute.
[0033] Preferably, the interaction between the modifier and the improver is used to improve the strength and toughness of the column.
[0034] Preferably, the curing temperature is controlled at 50° C., the curing humidity is maintained at 95%, and the curing time is not less than 48 hours.
[0035] Preferably, steam curing is added to the columns during the curing stage to enhance the internal structural stability of the material.
[0036] Compared with the prior art, the present invention provides a method for preparing ultra-high performance concrete railway protection fence posts, which has the following beneficial effects:
[0037] 1. The nano-alumina and graphite powder in the modifier can effectively improve the physical connectivity between the internal particles of the concrete, eliminating the need to use steel bars as support, avoiding the expansion, cracking and shedding of concrete caused by the corrosion of steel bars in the concrete, increasing the density and uniformity of the material, and thus improving the overall strength of the column. Secondly, the modified epoxy resin, as a reinforcing agent, further enhances the crack resistance of the column, allowing it to better absorb energy when impacted by external forces, reducing the generation and expansion of cracks. In addition, the silica fume component of the modifier increases the heat resistance of the material through chemical reactions, allowing the column to maintain structural stability in a high temperature environment, and the heat resistance is significantly improved compared to conventional materials.
[0038] 2. The addition of modifiers plays a significant reinforcing role in the preparation process of railway protective fence posts. First, the polycarboxylic acid water reducer and reinforced cellulose in the modifier can effectively improve the fluidity and density of concrete, so that the components can be more evenly distributed during the mixing process, reduce the porosity, and further improve the compressive strength of the material. Secondly, the addition of nano-silica promotes the microscopic interface reaction between the cementitious material and the aggregate, forming a denser structure, which significantly improves the crack resistance of the column. In addition, trace perovskite crystals stabilize the internal structure of the material during the curing process, thereby enhancing the material's heat resistance and deformation resistance.
[0039] 3. After the two additives were added at appropriate temperatures and time points, the heat resistance of the material was significantly enhanced, and the stability in high temperature environments was unexpectedly obtained. These improvements enable the columns to maintain their structural strength and durability when exposed to harsh environments for a long time, extending their service life. The optimized formula of modifiers and improvers can enhance the physical connection between different components, so that the columns still have high strength and excellent toughness without the use of steel bars. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the sample picture of ultra-high performance concrete after proportioning. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] Polycarboxylate water reducer in the modifier of the present invention: Polycarboxylate water reducer is a highly efficient water reducer that can reduce the amount of water used in concrete while maintaining good workability. It produces a steric hindrance effect by adsorbing on the surface of cement particles, reducing the mutual agglomeration between cement particles, thereby improving the fluidity and uniformity of concrete. It can improve the fluidity of concrete, reduce water consumption, improve the strength and density of concrete, reduce shrinkage cracks, and improve crack resistance.
[0043] Reinforced cellulose: Reinforced cellulose is an organic fiber material that is commonly used to enhance the toughness and crack resistance of concrete. In concrete, it can form a fiber network to absorb and disperse external stress and prevent the generation and expansion of cracks. By forming a fibrous network structure, it can significantly improve the crack resistance, bending resistance, and tensile resistance of concrete, especially under tensile or bending stress.
[0044] Nano-silicon dioxide: Nano-silicon dioxide is an ultra-fine particle material that can react chemically with calcium hydroxide in cement to generate more CSH gel (calcium silicate hydrate), increasing the strength and density of concrete. It improves the density of concrete, fills micropores, reduces porosity, increases compressive strength, significantly enhances durability, and improves crack resistance.
[0045] Trace perovskite crystals: Perovskite crystals are a material with a special crystal structure that can improve the heat resistance and corrosion resistance of concrete. Its unique lattice can improve the thermal stability of concrete and the physical and chemical structural stability of the material. It improves the heat resistance of concrete and enhances its anti-deformation ability, while maintaining the structural stability and strength of the material in high temperature environments.
[0046] Silica fume in the modifier of the present invention: Silica fume is a very fine volcanic ash material, mainly composed of silicon dioxide. It can fill the micro pores in concrete and react with calcium hydroxide produced during cement hydration to form CSH gel, further improving the strength and density of concrete. By reducing porosity and generating denser CSH gel, silica fume greatly improves the compressive strength and durability of concrete, while enhancing anti-permeability performance.
[0047] Graphite powder: Graphite powder has excellent thermal conductivity and lubricity, and can form a heat conduction channel in concrete, improving the thermal conductivity and high temperature resistance of concrete. Graphite powder can also enhance the wear resistance of the material. It can enhance the high temperature resistance and heat resistance of the material, while improving the electrical conductivity and thermal conductivity of concrete, which helps to improve the stability and deformation resistance of the overall material.
[0048] Nano-alumina: Nano-alumina is a high-strength, high-hardness material that can act as a reinforcing particle in concrete, significantly improving the material's compressive and crack resistance. Due to its nanoscale size, it can fill the tiny pores inside the concrete and increase its compactness. By filling the pores and improving the interface bonding force, nano-alumina significantly improves the concrete's compressive strength, crack resistance, and wear resistance, and also improves the material's durability.
[0049] Modified epoxy resin: Modified epoxy resin is a polymer material with excellent bonding and corrosion resistance. It can act as a binder in concrete, improve the bonding between the components, and enhance the toughness and crack resistance of concrete. By forming a tough mesh structure, modified epoxy resin improves the crack resistance, impact resistance and durability of concrete, while improving the material's water resistance and chemical corrosion resistance.
[0050] The compressive strength of the ultra-high performance concrete in the present invention should be measured according to the relevant provisions of GB / T50081 and should comply with the following provisions.
[0051] 1) 100 mmX100 mmX100 mm cubic specimens should be used, with 6 specimens in each group.
[0052] 2) The loading rate should be 1.20MPa / s~1.40MPa / s.
[0053] 3) Take the average strength value of the specimens with a deviation of less than 10% from the average value as the measured value. When the difference between 1 or 2 of the 6 measured values and the average value exceeds 10% of the average value, the measured values exceeding the average value by 10% shall be discarded, and the average value of the remaining measured values shall be taken as the compressive strength value of the group of specimens; when the strength values of 3 or more specimens deviate from the average value by more than 10%, the test results of the group of specimens are invalid.
[0054] The crack resistance test adopts GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The specific steps are as follows:
[0055] Step 1: Sample preparation: Prepare ultra-high performance concrete samples according to the formula, usually in the form of standard cubes or cylinders with a size of 100mmX100mmX400mm. After preparation, the samples should be cured under standard curing conditions, and the curing time is usually 28 days.
[0056] Step 2: Test equipment: The crack resistance test usually uses a crack width tester or a crack resistance tester. A four-point bending test device with a stress sensor can also be used to determine the crack formation of the material.
[0057] Step 3: Preliminary inspection: After the sample has cured for 28 days, a preliminary inspection is first carried out, including a visual inspection to ensure that there are no obvious cracks on the surface of the sample.
[0058] Step 4: Loading test: Place the sample on a four-point bending test device and gradually apply the load. The loading speed is generally 0.05 mm / min until the initial crack appears on the sample. Record the load and crack width at this time.
[0059] Step 5: Observation of crack formation: When visible cracks first appear on the sample surface, stop applying the load and measure the crack width, usually using a crack observation instrument or crack ruler, and record the maximum width of the crack and the load when the crack appears.
[0060] Step 6. Calculation of crack resistance index: Crack resistance is usually expressed by calculating the crack resistance index. The crack resistance index is calculated based on the ratio of the maximum tensile stress borne by the material to the stress when the material cracks. The formula is as follows: p=f1 / f2;
[0061] Among them, f1 is the maximum stress when the sample is damaged, f2 is the stress when the material first cracks, and p is the crack resistance index.
[0062] Step 7. Result analysis: According to the data measured in the test, calculate the percentage of improvement in crack resistance. The specific calculation formula is as follows: q= (p1-p0) / p0;
[0063] Among them, p1 is the anti-cracking index of the test sample, p0 is the anti-cracking index of the reference sample, and q is the improvement rate of the anti-cracking performance.
[0064] Heat resistance test: Partially refer to ISO 834 series international standards. In addition, for high-performance concrete high temperature resistance test, you can refer to GB / T50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete.
[0065] Crack resistance test standard: According to "JGJ / T 221-2010 Technical Specification for Application of Ultra-High Performance Concrete", the crack resistance test of concrete is carried out. By applying load or environmental stress to the specimen, observing the time when cracks occur and the width of cracks, the crack resistance of concrete is evaluated.
[0066] Durability test standard: Frost resistance test: Frost resistance test is carried out according to GB / T 50082-2009 Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete. The column specimens are placed in a freeze-thaw cycle device and subjected to 300 freeze-thaw cycles at a temperature of -20°C to 20°C to detect the mass loss rate and strength loss rate.
[0067] Impermeability test: According to the impermeability test in GB / T 50082-2009, the specimen is exposed to water pressure and the depth of water penetration is measured to evaluate the material's impermeability performance.
[0068] The test steps are as follows:
[0069] Step 1: Sample preparation: Prepare UHPC column samples of standard size, usually 10cm×10cm×10cm cubic test blocks or according to the actual component size. After curing for 28 days, use them for testing to ensure that the strength and structure of the material have reached a stable state.
[0070] Step 2: Pretreatment: The sample is placed at room temperature (about 25°C) to dry in advance to ensure that there is as little free water in the sample as possible during the test to prevent water vaporization from affecting the test data. Usually the pretreatment takes more than 24 hours.
[0071] Step 3: Temperature increase process: Place the sample in an electric furnace or high-temperature kiln for temperature increase test, and increase the temperature according to the following steps:
[0072] Slowly increase the temperature at a rate of 5°C / min, gradually raising it from room temperature to the target temperature (such as 900°C, 1000°C, 1200°C, etc.). This process can be adjusted according to specific test requirements.
[0073] Each target temperature is maintained for a period of time (usually 1 hour) to assess the stability of the material at that temperature.
[0074] Step 4: Observe and record: At the target temperature, observe and record the surface cracks, deformation and color changes of the sample.
[0075] Under high temperature, the sample surface will usually show phenomena such as falling off and cracking, but it is necessary to focus on observing whether there is significant strength attenuation or structural damage.
[0076] Step 5: Cooling process: After the target temperature test is completed, turn off the heating source and let the sample cool naturally to room temperature.
[0077] During the cooling process, structural changes in the sample, such as the occurrence of additional cracking or fragmentation, were recorded.
[0078] Step 6. Result analysis: The compressive strength change rate, crack formation and deformation of the sample at different temperatures will be used as the basis for judging its heat resistance.
[0079] The heat resistance limit of the material is evaluated based on indicators such as the proportion of compressive strength decay, crack length and width.
[0080] Spray humidification method: Use a spray device or humidifier to spray fine water mist on the surface of the concrete column to maintain the humidity in the air. The spray humidifier can run continuously to ensure that the air humidity reaches more than 95% during the curing period. It is suitable for indoor or closed spaces that need to control humidity for a long time. It is suitable for fine control of humidity and curing of small workpieces, and can provide a relatively uniform humidity environment.
[0081] Method of controlling humidity: Through continuous spraying or intermittent humidification, the water vapor content in the air is maintained at a high level, so that the concrete surface is always in a high humidity state, thereby maintaining the humidity of the concrete surface above 95%.
[0082] Steam curing uses the following steps:
[0083] First, the initially formed UHP concrete columns are placed in a closed steam curing room;
[0084] Then, saturated steam is introduced into the curing room to maintain the indoor temperature between 40-60°C and the humidity above 95%;
[0085] The steam curing time is then continued for 48-72 hours to ensure sufficient hydration of the concrete;
[0086] After the final curing is completed, the temperature is slowly lowered to room temperature, and the columns are removed for further processing.
[0087] Steam curing accelerates hydration reaction: Steam curing accelerates the hydration reaction of cement in concrete by increasing the ambient temperature (usually 40-60°C) and humidity (above 95%). The faster the hydration reaction, the faster the early strength of concrete increases. This is particularly beneficial to the construction period of the project, shortening the curing time while ensuring that the material achieves the required mechanical properties in a short time.
[0088] Steam curing in a high humidity and high temperature environment allows cement particles to hydrate faster, forming more CSH gel (calcium silicate hydrate), thereby significantly improving the compressive strength of concrete. Compared with traditional natural curing, ultra-high performance concrete columns after steam curing can reach or even exceed the designed compressive strength in a short time.
[0089] In a high humidity environment, the concrete has sufficient moisture inside, avoiding shrinkage cracks caused by early water loss. Steam curing can effectively reduce surface shrinkage cracks caused by rapid water loss, improve the crack resistance of the column, and ensure that the material maintains good volume stability during the curing period.
[0090] Improve the density and durability of materials: Steam curing promotes the complete hydration of cement particles through high temperature, reduces the unhydrated cement particles and micropores in the material, thereby improving the density of ultra-high performance concrete. After the density of the material is increased, not only the compressive strength is improved, but also its impermeability and frost resistance are effectively enhanced, extending the service life of the material.
[0091] Since steam curing is carried out in a high temperature environment, the material is pre-treated under high temperature conditions to form a more stable internal structure. This structural stability enables the UHPC columns to exhibit better heat resistance in subsequent high temperature environments (such as fire or extreme climate conditions) and effectively maintain their mechanical properties.
[0092] Steam curing not only accelerates the hydration reaction, but also optimizes the internal microstructure of concrete, making the cement matrix more uniform and dense. Especially when using modifiers and modifiers, steam curing further enhances the bonding between the nano-scale reinforcing components and the matrix, significantly improving the toughness and deformation resistance of the material.
[0093] The mixing equipment used in the present invention is a high-performance concrete mixer (model: JS1500 twin-horizontal shaft concrete mixer), the steam curing equipment is a steam curing box (model: YH-40 steam curing box), the flexural strength testing equipment is a concrete compressive strength testing machine (model: YES-2000 digital hydraulic compression testing machine), the freeze-thaw testing equipment is a concrete freeze-thaw cycle testing machine (DRC-300 freeze-thaw cycle testing box), and the spray humidification equipment is an ultrasonic spray humidifier (JCS-30 ultrasonic industrial humidifier). The above equipment is a usable model, not the only model. It is sufficient to use equipment that can meet the use requirements of the present invention, and no further description is given here. Example
[0094] The preparation method of ultra-high performance concrete railway protection fence posts specifically comprises the following steps:
[0095] Prepare the raw materials by weight group ratio:
[0096] Cement: 350 parts; microsilica powder: 50 parts; quartz sand: 800 parts; improver: 15 parts; modifier: 10 parts; water: 120 parts; water reducing agent: 5 parts.
[0097] The modifier is mixed in proportion by weight: silica fume: 35 parts, graphite powder: 15 parts, nano-alumina: 20 parts, and modified epoxy resin: 10 parts.
[0098] The modifiers are mixed in proportion by weight: polycarboxylic acid water reducer: 25 parts; reinforced cellulose: 20 parts; nano silicon dioxide: 15 parts; trace perovskite crystals: 5 parts.
[0099] Stir at 20℃ for 30 minutes, add improver at 25℃, add modifier after stirring for 10 minutes, stir thoroughly, pour into the mold, let stand to form, cure at 50℃, in an environment with 95% humidity for 48 hours, and solidify to obtain columns. Example
[0100] The preparation method of ultra-high performance concrete railway protection fence posts specifically comprises the following steps:
[0101] Prepare the raw materials by weight group ratio:
[0102] Cement: 360 parts; microsilica powder: 60 parts; quartz sand: 820 parts; improver: 18 parts; modifier: 13 parts; water: 125 parts; water reducing agent: 6 parts.
[0103] The modifier is mixed in proportion by weight: silica fume: 36 parts, graphite powder: 16 parts, nano-alumina: 22 parts, and modified epoxy resin: 11 parts.
[0104] The modifiers are mixed in proportions by weight: polycarboxylic acid water reducer: 27 parts; reinforced cellulose: 23 parts; nano silicon dioxide: 16 parts; trace perovskite crystals: 6 parts.
[0105] Stir at 20℃ for 30 minutes, add improver at 30℃, add modifier after stirring for 10 minutes, stir thoroughly, pour into the mold, let stand to form, cure at 50℃, in an environment with 96% humidity for 48 hours, and solidify to obtain columns. Example
[0106] The preparation method of ultra-high performance concrete railway protection fence posts specifically comprises the following steps:
[0107] Prepare the raw materials by weight group ratio:
[0108] Cement: 370 parts; microsilica powder: 80 parts; quartz sand: 860 parts; improver: 26 parts; modifier: 16 parts; water: 130 parts; water reducing agent: 8 parts.
[0109] The modifier is mixed in proportion by weight: silica fume: 38 parts, graphite powder: 17 parts, nano-alumina: 23 parts, and modified epoxy resin: 13 parts.
[0110] The modifiers are mixed in proportions by weight: polycarboxylic acid water reducer: 32 parts; reinforced cellulose: 27 parts; nano silicon dioxide: 18 parts; trace perovskite crystals: 8 parts.
[0111] Stir at 20℃ for 30 minutes, add improver at 25℃, add modifier after stirring for 10 minutes, stir thoroughly, pour into the mold, let stand to form, cure at 50℃, in an environment with 95% humidity for 48 hours, and solidify to obtain columns. Example
[0112] The preparation method of ultra-high performance concrete railway protection fence posts specifically comprises the following steps:
[0113] Prepare the raw materials by weight group ratio:
[0114] Cement: 400 parts; microsilica powder: 100 parts; quartz sand: 900 parts; improver: 30 parts; modifier: 20 parts; water: 140 parts; water reducing agent: 10 parts.
[0115] The modifier is mixed in proportion by weight: silica fume: 40 parts, graphite powder: 20 parts, nano-alumina: 25 parts, and modified epoxy resin: 15 parts.
[0116] The modifiers are mixed in proportion by weight: polycarboxylic acid water reducer: 35 parts; reinforced cellulose: 30 parts; nano silicon dioxide: 20 parts; trace perovskite crystals: 10 parts.
[0117] Stir at 20℃ for 30 minutes, add improver at 30℃, add modifier after stirring for 10 minutes, stir thoroughly, pour into the mold, let stand to form, cure at 50℃, in an environment with 96% humidity for 48 hours, and solidify to obtain columns.
[0118] Comparative Example 1:
[0119] No modifier was added, and the rest was the same as in Example 1.
[0120] Comparative Example 2:
[0121] No improver was added, and the rest was the same as in Example 1.
[0122] Comparative Example 3:
[0123] No modifier or improver is added, and the rest is the same as in Example 1.
[0124] Seven groups of column products in Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3 were taken for compressive strength, crack resistance and heat resistance tests, respectively. Each group of test products had 6 products, and the average value of the test results was taken. The specific test results are as follows:
[0125] Table 1. Performance test results of Examples 1-4 and Comparative Examples 1-3
[0126]
[0127] It can be seen from the experimental results that the railway protection fence posts prepared in Examples 1 to 4 are significantly better than those in Comparative Examples 1 to 3 in terms of compressive strength, crack resistance and heat resistance. In particular, the introduction of modifiers and improvers significantly improves the crack resistance of the material, while greatly improving the heat resistance and compressive strength, effectively improving the structural strength of the posts.
[0128] Seven groups of column products in Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3 were taken, and the bending strength, frost resistance and impermeability tests were performed respectively. Each group of test products had 6 products, and the average value of the test results was taken. The specific test results are as follows:
[0129] Table 2. Performance test results of Examples 1-4 and Comparative Examples 1-3
[0130]
[0131] It can be seen from the experimental results that the railway protection fence posts prepared in Examples 1 to 4 are significantly better than those in Comparative Examples 1 to 3 in terms of bending strength, frost resistance and impermeability. In particular, the introduction of modifiers and improvers significantly improves the frost resistance of the material, while the impermeability and bending strength are greatly improved, effectively improving the structural strength and durability of the posts.
[0132] Additional Note: The modifier is added to the concrete mixture after the initial mixing of cement, microsilica powder, quartz sand and water. The mixing time should be controlled within 15-20 minutes to ensure that the modifier can be fully combined with other components in the mixture.
[0133] The time to add the modifier is chosen after the initial mixing of the raw materials to ensure that it can be fully dispersed in the mixture. The ingredients in the modifier, such as nano-alumina and graphite powder, need time to fully enter the pores in the cement matrix and form a more stable physical and chemical connection. Adding the modifier early in the mixing process allows it to fully react with the cement particles and enhance the microstructure of the material.
[0134] Therefore, the early addition of modifiers helps to improve the microstructure inside the guardrail posts, reduce the porosity in the cement matrix and enhance its density. Nano-scale components such as nano-alumina improve compressive strength by filling microscopic pores and reducing the macroporous structure generated during the hydration reaction. In addition, ingredients such as graphite powder can increase the thermal conductivity of the material, thereby improving heat resistance. In this way, the modifier not only strengthens the physical connection of the material, but also optimizes its durability.
[0135] The modifier is added within about 5-10 minutes after the modifier is evenly mixed, and is continuously mixed under low-speed stirring conditions to ensure that the modifier components are fully integrated with other components. The addition of the modifier requires controlled stirring speed and time so that it can be effectively dispersed into the concrete matrix.
[0136] The addition of the modifier is chosen after the modifier is fully combined with the substrate, which can avoid the destruction of the modifier components during the stirring process and ensure that it can react optimally with the particles in the mixture. The time of adding the modifier is very critical. Adding it too early may lead to incomplete reaction, while adding it too late may affect the uniformity of the mixture.
[0137] Therefore, the introduction of modifiers can further optimize the toughness and ductility of the guardrail posts. Its components such as polycarboxylate water reducer and nano-silica enhance the material's resistance to cracking and deformation by forming a more uniform and dense distribution in the matrix. In addition, the reinforcing cellulose in the modifier significantly improves the material's resistance to cracking and bending by forming a fibrous network structure in the matrix. These reinforcing ingredients improve the material's ductility and deformation resistance by refining the pore structure in the cement matrix.
[0138] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-high performance concrete railway protection fence column, characterized in that: The following steps are involved: a) Prepare the following raw materials by weight: Cement: 350-400 parts; Microsilica fume: 50-100 parts; Quartz sand: 800-900 parts; Improver: 15-30 parts; Modifier: 10-20 parts; Water: 120-140 parts; Water reducing agent: 5-10 parts; b) During the mixing process, cement, microsilica powder, quartz sand and water are added in the initial stage and stirred evenly; c) Add the improver at a temperature of 25-30°C and continue stirring for 10-15 minutes; d) After 10 minutes of stirring, add the modifier and keep stirring to allow the modifier to fully blend with other components; e) Pour concrete and let it stand to form, in an environment with a curing temperature of 40-60°C and a curing humidity of not less than 95%, and the curing time is not less than 48 hours; f) After curing, the obtained column material has good crack resistance, deformation resistance and heat resistance; The improver comprises the following components in proportion by weight: Silica fume: 35-40 parts; Graphite powder: 15-20 parts; Nano-alumina: 20-25 parts; Modified epoxy resin: 10-15 parts; The components are mixed by stirring evenly and heating to 50°C-60°C, then cooled and stirred evenly before use; The modifier comprises the following components in parts by weight: Polycarboxylate water reducer: 25-35 parts; Reinforced cellulose: 20-30 parts; Nano silicon dioxide: 15-20 parts; Trace perovskite crystals: 5-10 parts.
2. The method for preparing the ultra-high performance concrete railway protection fence column according to claim 1, characterized in that: The improver is added at a temperature of 25-30°C, and the stirring time is controlled at 10-15 minutes to ensure full fusion of the components.
3. The method for preparing the ultra-high performance concrete railway protection fence column according to claim 1, characterized in that: The modifier is added 5-10 minutes after the improver, and the stirring speed is controlled at 100 revolutions per minute.
4. The method for preparing the ultra-high performance concrete railway protection fence column according to claim 1, characterized in that: The interaction of the modifier and improver is used to improve the strength and toughness of the column.
5. The method for preparing the ultra-high performance concrete railway protection fence column according to claim 1, characterized in that: The curing temperature is controlled at 50° C., the curing humidity is maintained at 95%, and the curing time is not less than 48 hours.
6. The method for preparing the ultra-high performance concrete railway protection fence column according to claim 1, characterized in that: The columns are subjected to steam curing during the curing stage to enhance the internal structural stability of the material.
